Ambient Ammonia Electrosynthesis from Nitrogen and Water by Incorporating Palladium in Bimetallic Gold–Silver Nanocages. Issue 5 (3rd February 2020) - Nazemi, Mohammadreza; Soule, Luke; Liu, Meilin; El-Sayed, Mostafa A.
Abstract : Electrosynthesis of ammonia using nitrogen and water provides a potential alternative to the thermochemical process (Haber-Bosch) in a clean, sustainable, and decentralized way when electricity is generated from renewable sources. To enable the widespread commercialization of this technology, an electrocatalyst to convert nitrogen (N2 ) to ammonia (NH3 ) with high selectivity and activity must be developed. Here, we report our findings in the investigation into the role of incorporating palladium (Pd) in bimetallic Au-Ag nanocages on the electrocatalytic activity of the nitrogen reduction reaction (NRR) under ambient conditions. The localized surface plasmon resonance (LSPR) peak position of the resulting trimetallic nanoparticles is tuned with Pd concentration, achieving the highest electrocatalytic NRR activity (NH3 yield rate = 5.80 μ g cm −2 h −1, Faradaic efficiency = 48.94%) using Au-Ag-Pd-850 nanoparticles at −0.3 V vs RHE. This activity corresponds to the production energy efficiency of 28.9% with an electrical energy input of 19.1 MWh / ton NH3 . The enhanced NRR activity is attributed mainly to the formation of a highly porous Pd layer with remarkably high surface area active for NRR. In addition, operando surface-enhanced Raman spectroscopy (SERS) is used to probe the mechanism of NRR on the trimetallic nanostructures and to identify the intermediate species at the electrode-electrolyte interface.